2018
DOI: 10.1007/s10734-018-0320-8
|View full text |Cite
|
Sign up to set email alerts
|

Turn up, tune in, don’t drop out: the relationship between lecture attendance, use of lecture recordings, and achievement at different levels of study

Abstract: Lecture capture tends to polarise the views of academic staff. Some view it as encouraging non-attendance at lectures. Others view it as a valuable adjunct, allowing students to revisit the lecture experience and providing opportunities for clarification and repetition of key points. However, data supporting either of these stances remains scarce. Irrespective of these views, a more pertinent question pertains to the impact of lecture attendance and the use of recordings on student achievement. Findings remain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 38 publications
(50 reference statements)
1
47
0
Order By: Relevance
“…A meta-analysis by Danielson et al (2014) indicates that results in the literature are mixed. Some studies found that there was no clear relationship between learning outcomes and lecture capture use (Spickard et al 2002, Solomon et al 2004, Brotherton and Abowd 2004, Bacro et al 2010, Franklin et al 2011 However, non-attendees that watched LC did have better exam results than students who neither attended class nor watched the videos (Inglis et al 2011, Williams et al 2012, Nordmann et al 2018. As a footnote, it should be mentioned that a reported limitation of these studies was that the attendance and viewing data may be subject to inaccuracies.…”
Section: Does Lc Positively Affect Learning?mentioning
confidence: 94%
See 3 more Smart Citations
“…A meta-analysis by Danielson et al (2014) indicates that results in the literature are mixed. Some studies found that there was no clear relationship between learning outcomes and lecture capture use (Spickard et al 2002, Solomon et al 2004, Brotherton and Abowd 2004, Bacro et al 2010, Franklin et al 2011 However, non-attendees that watched LC did have better exam results than students who neither attended class nor watched the videos (Inglis et al 2011, Williams et al 2012, Nordmann et al 2018. As a footnote, it should be mentioned that a reported limitation of these studies was that the attendance and viewing data may be subject to inaccuracies.…”
Section: Does Lc Positively Affect Learning?mentioning
confidence: 94%
“…Attendance data and LC viewing data gathered was either student self-reported or through the technologies' tracking systems, which reported the number of LC views but did not report number of minutes viewed. Therefore, it was impossible to know whether number of "views" logged, were by students watching the LC to completion, or for just for a few seconds (Nordmann et al 2018). Therefore it could be that low marks are not due to LC being a less effective substitute, but more due to low effort (poor attendance and ineffective lecture capture review).…”
Section: Does Lc Positively Affect Learning?mentioning
confidence: 99%
See 2 more Smart Citations
“…However, reported studies can be very useful in suggesting factors that merit investigation in other contexts. For example, a recent learning analytics study concerning the impact of attendance and use of LC recordings on attainment (Nordmann et al 2018) highlights that prior attainment and year of study are also important factors to consider.…”
Section: What Can We Learn From Learning Analytics?mentioning
confidence: 99%